Fueling recognition of opportunities through innovative behavior: Mediating role of team entrepreneurial passion and team innovation capacity - Rocio Romani-Torres; Diego Norena-Chavez (Cogent Business & Management, 2023)
Opportunities recognition is a crucial predictor to assess the viability of any business in a competitive, changing, and uncertain market. In this context, researchers have emphasized innovative behavior should be examined as a driver to recognize opportunities. Despite the growing interest in research on the impact of innovative behavior on the recognition of opportunities, studies are surprisingly scarce. This study seeks to determine how innovative behavior impacts on the recognition of opportunities through team entrepreneurial passion and team innovation capacity in a post-pandemic framework, supporting the mediating effects by resource-based vision theory and opportunity recognition theory. Data were collected in face-to-face surveys to 601 decision-makers of small and medium-sized enterprises (SMEs) in a textile cluster in Lima, Peru using a cross-sectional research design by partial least squares structural equation modeling (PLS-SEM). The findings show that (1) innovative behavior has a positive and significant effect on the recognition of opportunities, and (2) team entrepreneurial passion and team innovation capacity mediate this relationship. These finding enrich the theories and the result can serve as the highlights for management, policies designed for innovative behavior, team entrepreneurial passion, and team innovation capacity in business that generates a competitive advantage especially in developing countries.
Keywords: 650; innovative behavior; recognition of opportunities; SMEs; team entrepreneurial passion; team innovation capacity